Congreso Internacional de Educación a Distancia. (UNED, 2023)
Aparece Rodrigo Arias con compañeros de la Oficina de Audiovisuales: Luis Fernando Fallas, Lucía Osorio Torrico, Adriana Oviedo, Javier Alpízar, Abraham Montoya, Adalberto Blanco